Discussion on Allowable Values of Deviations with ISO 1328-1:2013 and ISO 1328-2:2020 - Li Haixia; Fan Ruili; Wang Zhigang; Guan Hongjie (Jixie chuandong)
The second edition of ISO 1328-2 was released in 2020, which adjusted the scope of application and modified the evaluation system of accuracy level to distinguish it from ISO 1328-1. In order to better understand and apply the gear accuracy standard, the author starts with the change of the standard name and calculation rules of the deviation allowable values, and analyzes the relationship between the differences of each deviation item and the dependent variables in the first and second editions of ISO 1328-1 with the help of the modulus mn, the diameter d of the dividing circle and other variables. At the same time, the author analyzes and compares the new and old editions of ISO 1328-2 in the scope of application, tolerance classification and deviation items and differences in the determination methods of allowable deviation values. The results show that the first and second editions are quite different and should be paid attention to.